How does government regulations and institutional decisions affect our wildlife, communities and green economy? - Kitshoff-Botha, Adri, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
There were trends over the past few years where decisions by Governments, wildlife services and parastatals had a direct negative effect on our wildlife, communities and green economy. These included bans on trophy hunting, imports and transports. On the other hand, there are also government departments introducing enabling legislation to the benefit of our wildlife and communities.
How do government regulations and institutional decisions affect our wildlife, communities and green economy?
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.